MEREDUKSI TURNOVER INTENTION KARYAWAN FINANCE (STUDI KASUS PADA PT. CENTRAL SANTOSA FINANCE CABANG SEMARANG) - Aprih Santoso; Mohamad Ashar Amin (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
Human resources are the main mover in a company. The key to the success of a company lies in human resources, namely as the initiator, energizer, creativity and their efforts to the organization on an ongoing basis. This research was conducted at PT. Central Santosa Finance Semarang Branch Field Collection Section with the aim to determine the effect of job stress, compensation, leadership and organizational commitment to turnover intention. The research sample consisted of 37 people using the census method. The analysis used is multiple linear regression analysis. The results showed that job stress, compensation, leadership, organizational commitment had a positive and significant effect on turnover intention.